Improving Pancasila Education Learning Outcomes through Educational Games-Based Discovery Learning Model in Grade III Elementary School Students - Kumala, Farida Nur; Azizah, Evi Dwi; Ayudhanti, Famia (Actual Insight, 2025)
The material Let's Get to Know Pancasila is part of Pancasila Education taught to third-grade elementary school students. This material is often considered too broad, which creates obstacles for students in understanding the core values of Pancasila. Furthermore, the use of suboptimal learning models and media contributes to low student learning outcomes. This study aims to improve student learning outcomes through the application of the Discovery Learning model integrated with educational games. The research employed Classroom Action Research with a single-case study design, conducted in three stages: pre-cycle, cycle I, and cycle II, following the stages of planning, implementation, observation, and reflection. The research subjects consisted of 26 students in Grade III-C at Sekolah Dasar Negeri Gadang 1, Malang City. Data were collected through learning outcome tests, interviews, observations, and documentation. The results indicated a significant improvement in student learning outcomes, from a completion rate of 42.31 percent (average score 63.70) in the pre-cycle, to 73.08 percent (average score 75.19) in the first cycle, and 88.46 percent (average score 85.56) in the second cycle. The novelty of this study lies in integrating the Discovery Learning model with educational games in teaching Pancasila Education at the elementary school level, an area that has been rarely explored. These findings demonstrate that interactive and student-centered learning approaches can effectively enhance comprehension of complex civic values.